Does mobile phone ownership predict better utilization of maternal and newborn health services? a cross-sectional study in Timor-Leste. Issue 1 (December 2016) - Nie, Juan; Unger, Jennifer; Thompson, Susan; Hofstee, Marisa; Gu, Jing; Mercer, Mary
Abstract Background Increasingly popular mobile health (mHealth) programs have been proposed to promote better utilization of maternal, newborn and child health services. However, women who lack access to a mobile phone are often left out of both mHealth programs and research. In this study, we determine whether household mobile phone ownership is an independent predictor of utilization of maternal and newborn health services in Timor-Leste. Methods The study included 581 women aged 15–49 years with a child under the age of two years from the districts of Manufahi and Ainaro in Timor-Leste. Participants were interviewed via a structured survey of knowledge, practices, and coverage of maternal and child health services, with additional questions related to ownership and utilization of mobile phones. Mobile phone ownership was the exposure variable, and the dependent variables included having at least four antenatal care visits, skilled birth attendance, health facility delivery, a postnatal checkup within 24 h, and a neonatal checkup within 24 h for their youngest child. Logistic regression models were applied to assess for associations. Results Sixty-seven percent of women reported having at least one mobile phone in the family. Women who had a mobile phone were significantly more likely to be of higher socioeconomic status and to utilize maternal and newborn health services. However, after adjusting socioeconomic factors, household mobile phone ownership was not independently associated with any of the dependent variables. Conclusion Evaluations of the effects of mHealth programs on health in a population need to consider the likelihood of socioeconomic differentials indicated by mobile phone ownership.